2006
DOI: 10.1089/jwh.2006.15.1214
|View full text |Cite
|
Sign up to set email alerts
|

Anger, Hostility, and Cardiac Symptoms in Women with Suspected Coronary Artery Disease: The Women's Ischemia Syndrome Evaluation (WISE) Study

Abstract: Among women with suspected CAD, anger-out scores were associated with the presence of angiographic CAD. Anger/hostility traits were associated with increased symptoms, particularly with nonanginal chest pain in women without angiographic CAD. Relationships among psychosocial factors, cardiac symptoms, and angiographic CAD are potentially important in the management of women with suspected CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 40 publications
0
29
1
2
Order By: Relevance
“…A tentative explanation for the discrepancy between findings regarding anger-out and CHD from previous investigations and our and Krantz's recent study [33] may be that with the approaching of gender roles we are witnessing in modern societies -probably even more so in Sweden -the way women and men express their anger and therefore the associated risk may also tend to converge.…”
Section: Comparison With Previous Studiescontrasting
confidence: 82%
See 2 more Smart Citations
“…A tentative explanation for the discrepancy between findings regarding anger-out and CHD from previous investigations and our and Krantz's recent study [33] may be that with the approaching of gender roles we are witnessing in modern societies -probably even more so in Sweden -the way women and men express their anger and therefore the associated risk may also tend to converge.…”
Section: Comparison With Previous Studiescontrasting
confidence: 82%
“…The findings of Siegman et al [21] also indicate that subtle, indirect manifestations of antagonism are stronger predictors of CHD risk in women than in men, while overt expressions of anger confer higher risk in men compared to women. However, a recent study involving women with suspected CHD found no association between anger suppression and presence of angiographic CHD [33]. In the only study in which female patients were included in a high enough number to allow analysing the effect of anger expression on prognosis following an acute cardiac event among women [18] no relationship was found between suppression of anger and long-term prognosis.…”
Section: Comparison With Previous Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…A cardiac symptom list adapted from the Women and Ischemia Syndrome Evaluation study (WISE) 24 was used to assess the presence and intensity of ten cardiac symptoms (chest pain/pressure, palpitations, dizziness/ lightheadedness, sweating, jaw pain, arm/ shoulder pain, weakness, nausea, and indigestion). Total number of symptoms were recorded, as well as severity of each symptom [1][2][3] to allow a measure of both number (maximum scoreϭ10) and intensity (maximum scoreϭ30) of symptoms.…”
Section: Physical Health Outcomesmentioning
confidence: 99%
“…The Women's Ischemia Syndrome Evaluation (WISE) study assessed female ischemic heart disease pathophysiology and how sex hormones and other gender-specific findings influence clinical aspects of the disease. In this study, women referred for angiograms due to chest pain and suspected ischemia were enrolled to assess their frustration, increased aggression and anger (131). Although anger and hostility are not predictive of coronary artery disease in women, those who express anger may be at increased risk if they also have other risk factors such as age, history of diabetes, and elevated serum lipid levels.…”
Section: Stress and Psychosocial Factorsmentioning
confidence: 99%